Black Carbon and Elemental Carbon from Postharvest Agricultural-Waste Burning Emissions in the Indo-Gangetic Plain. (26th February 2014) - Singh, Atinderpal; Rajput, Prashant; Sharma, Deepti; Sarin, M. M.; Singh, Darshan
Abstract : We compare the mass concentrations of black carbon (BC) and elemental carbon (EC) from different emissions in the Indo-Gangetic Plain (IGP), using optical (Aethalometer; 880 nm) and thermooptical technique (EC-OC analyzer; 678 nm), respectively. The fractional contribution of BC mass concentration measured at two different channels (370 and 880 nm), OC/EC ratio, and non-sea-salt K + /EC ratios have been systematically monitored for representing the source characteristics of BC and EC in this study. The mass concentrations of BC varied from 8.5 to 19.6, 2.4 to 18.2, and 2.2 to 9.4 μ g m −3 during October-November (paddy-residue burning emission), December–March (emission from bio- and fossil-fuel combustion) and April-May (wheat-residue burning emission), respectively. In contrast, the mass concentrations of EC varied from 3.8 to 17.5, 2.3 to 8.9, and 2.0 to 8.8 μ g m −3 during these emissions, respectively. The BC/EC ratios conspicuously greater than 1.0 have been observed during paddy-residue burning emissions associated with high mass concentrations of EC, OC, and OC/EC ratio. The Ångström exponent (α ) derived from Aethalometer data is approximately 1.5 for the postharvest agricultural-waste burning emissions, hitherto unknown for the IGP. The mass absorption efficiency (MAE) of BC and EC centers at 1–4 m 2 g −1 and 2-3 m 2 g −1 during the entire study period in the IGP.